2085. Evaluation of Panther Fusion Flu A/B/RSV, AdV/hMPV/RV and Paraflu Assays for the Detection of Respiratory Viruses in Children. (26th November 2018) - Hassan, Ferdaus; Crawford, Jordan; Banerjee, Dithi; Selvarangan, Rangaraj
Abstract: Background: There are many FDA cleared multiplexed respiratory assays available in the United States, ranging from 3 to 20 targets per assay. FilmArray Respiratory Panel (RP) is one of the mega-multiplexed assay, includes 20 targets and results are available in 1 hour. Recently Hologic has received FDA-clearance for several smaller respiratory "Panther Fusion assays" (3–4 targets/assay) and results are available in <3 hours. The aim of this study was to evaluate the performance of three panther fusion multiplexed assays: (i) Flu A/B/RSV assay, (ii) adenovirus/human metapneumovirus/rhinovirus assay, and (iii) paraflu (parainfluenza virus 1–4) assay in comparison to RP assay. Methods: A total of 194 frozen nasopharyngeal swab samples (from 2016 to 2018) obtained from children aged ≤18 years and previously tested by RP as a routine clinical testing were included in this study. These samples were tested by all three fusion assays. Positive percent agreement (PPA) and negative percent agreement (NPA) of Fusion assays were calculated against RP assay. Results: Among 194 samples, 58.0% were from male. Median age was 36 months (IQR 13–72 months). Overall agreement between two assays was 82.5% (95% CI 77.6–88.1). PPA and NPA of Fusion assays for each target was; Flu A-100.0% and 100.0%, Flu B-95.0% and 100.0%, RSV-90.1% and 94.0%, adenovirus-80.0% and 98.2%, hMPV-95.2% and 99.4%, Rhino-79.1% and 95.8%, Parainfluenza virus-100.0 and 100.0%, respectively. There were total 34 discrepant samples. Among these, majority were rhino ( n = 12), RSV ( n = 12) and adenovirus ( n = 7). Of 12 rhinovirus discrepant samples, Fusion assay detected additional seven but missed five samples. For 12 RSV discrepant samples, fusion assay detected 10 more RSV but missed two. Fusion assay missed four adenoviruses and detected additional three samples. All discrepant samples, especially rhinovirus positive samples need further investigation since RP detects both rhinovirus and enterovirus, whereas the Fusion assay detects rhinovirus only. Conclusion: Performance of fusion Flu A/B/RSV and Paraflu assays were comparable with RP assays. Fusion AdV/hMPV/RV assay had the highest discrepancy with RP assay. Overall, Panther fusion respiratory assays provide the opportunity to customize testing with smaller respiratory panels at a reduced cost. Disclosures: All authors: No reported disclosures.